2019
DOI: 10.1038/s41598-019-45125-y
|View full text |Cite
|
Sign up to set email alerts
|

A 30 Gb/s PAM4 underwater wireless laser transmission system with optical beam reducer/expander

Abstract: We have, so far as we know, proposed and demonstrated the first 30 Gb/s four-level pulse amplitude modulation (PAM4) underwater wireless laser transmission (UWLT) system with an optical beam reducer/expander over 12.5-m piped underwater channel/2.5-m high-turbidity harbour underwater channel. In piped underwater links, the performances of PAM4 UWLT systems get better with beam reduction given a small amount of light absorbed by the piped water. In highly turbid harbour underwater links, the performances of PAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 33 publications
(25 reference statements)
0
25
0
Order By: Relevance
“…In this study, a 500-Gb/s PAM4 FSO-UWOC convergent system through 100 m free-space transmission with either 10 m piped underwater link or 5 m turbid underwater link is proposed, employing a red/green/blue (R/G/B) five-wavelength polarization-multiplexing scheme as an illustration. In piped underwater links, the overall attenuation coefficients at 450.6 nm (blue-light), 488.2 nm (blue-light), and 520.4 nm (green-light) are lower than those at 642.6 nm and 660.3 nm (red-light) [11]- [14]. 450.6 nm blue-light, 488.2 nm bluelight, and 520.4 nm green-light laser diode (LD) with twostage light injection and optoelectronic feedback techniques are thereby utilized in a 110-m FSO-UWOC convergence.…”
Section: Introductionmentioning
confidence: 93%
“…In this study, a 500-Gb/s PAM4 FSO-UWOC convergent system through 100 m free-space transmission with either 10 m piped underwater link or 5 m turbid underwater link is proposed, employing a red/green/blue (R/G/B) five-wavelength polarization-multiplexing scheme as an illustration. In piped underwater links, the overall attenuation coefficients at 450.6 nm (blue-light), 488.2 nm (blue-light), and 520.4 nm (green-light) are lower than those at 642.6 nm and 660.3 nm (red-light) [11]- [14]. 450.6 nm blue-light, 488.2 nm bluelight, and 520.4 nm green-light laser diode (LD) with twostage light injection and optoelectronic feedback techniques are thereby utilized in a 110-m FSO-UWOC convergence.…”
Section: Introductionmentioning
confidence: 93%
“…Hong et al probed probabilistic constellation shaping in a DMT-based UOWC system to approach the underwater channel capacity limit, and the net data rate was pushed to 18.09 Gbps over a 5-m water channel with a single LD [13,14]. Injectionlocking and optoelectronic feedback techniques were introduced to enhance the frequency response of the UOWC system using two LDs and two avalanche photodiodes (APDs) [15], where a 30-Gbps/ 2.5-m wireless transmission system in a high-turbidity harbor water channel was experimentally demonstrated. Wang et al experimentally demonstrated a 100-m/ 500-Mbps underwater optical wireless transmission system using non-return-to-zero onoff keying (NRZ-OOK) modulation and nonlinear equalization with a 520-nm LD [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, GaN-based laser diodes (LDs) are a potentially key component in visible light communication (VLC) systems, with higher modulation bandwidth and output power capabilities compared to their LED counterparts. Standard Fabry-Perot (FP) GaN LDs have shown high bandwidths, allowing communication at data rates of multiple gigabits per second [2,3]. However, for many applications, such as cold atom systems [4], spectroscopy [5], medical diagnostics [6], and underwater optical communications [7,8], spectral purity and the ability to select and tune specific wavelengths is extremely important [9].…”
Section: Introductionmentioning
confidence: 99%